Diverse roles for occupational therapists - Clewes, Jane; Kirkwood, Robert (Occupational therapist) (M & K Publishing, 2016)
This book covers a range of roles for occupational therapists. Authors show how they have embraced opportunities, extended roles, and developed services along with the ever-changing world of statutory services.